Implementation of a Waste Filtration Control System and Monitoring of Waste Quality in an Internet of Things-Based Laundry Business - Pio, Priska; Dwi Suarjaya, I Made Agus; Buana, Putu Wira (Program Studi Teknologi Informasi, Fakultas Teknik, Universitas Udayana, 2025)
An Internet of Things (IoT)-based wastewater filtration control system is developed to monitor water quality in real-time and automatically manage the filtration process. pH, turbidity, and Total Dissolved Solids (TDS) sensors are employed to detect the quality of wastewater generated from laundry a This section presents the results of the design and implementation stages of the waste filtration control system and Internet of Things-based water quality monitoring. ctivities. Sensor data is transmitted via Arduino and ESP8266 microcontrollers to Firebase, then displayed through an Android application. Based on the sensor readings, the system activates the filtration pump or channels the water to either a drainage outlet or a storage tank depending on the water condition. Test results indicate a 70% success rate in producing cleaner water from ten tested samples. The system also demonstrates stable and fast data transmission to Firebase and the Android application. This solution is suitable for small-scale applications, especially for household and laundry wastewater management.